The Impact of Web Design, Customer Service, Security, and Fulfillment towards Customer Satisfaction of Online Shoppers Platform(Case Study:Sam Ratulangi Manado) - Triska Prisilia Rawung; Paulus Kindangen; Ferdinand Tumewu (Universitas Sam Ratulangi, 2022)
The purpose of this research is to evaluating Impact of Web Design, Customer Service, Security, and Fulfillment towards Customer Satisfaction of Online Shoppers Platform in Sam Ratulangi Manado. This research used quantitative method. 100 samples were collected with questionnaire distributed to the Sam Ratulangi University Students. The result of this research shows that Web design, Customer Service, Security, Fulfillment have a positive and significant influence on customer satisfaction on online shoppers platform on the customers in Sam Ratulangi University in Manado and 6 points Likert scale was used to help the data analysis in this research for the Impact of Web Design, Customer Service, Security, and Fulfillment towards Customer Satisfaction of Online Shoppers Platform.